2017
DOI: 10.1017/s0263034617000581
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a circularly polarized laser beam in an obliquely magnetized plasma channel

Abstract: The evolution of the spot size and amplitude of a circularly polarized laser beam propagating in a plasma channel embedded in an obliquely applied magnetic field has been investigated. The wave equation describing the evolution of the radiation field is set up and a variational technique is used to obtain the equations governing the evolution of the spot size and amplitude. Numerical methods are used to analyze the evolution of the laser beam spot size and amplitude. It is seen that the amplitudes of the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Gupta et al reported that the combined effect of a plasma density ramp and a magnetic field enhances the self‐focusing property of the laser beam. Theoretical investigations reveal that the presence of axial magnetic field not only decreases the laser spot size, but enhances the self‐focusing property of the circularly polarized and the linearly polarized laser beam . Sharma and Tripathi have investigated the relativistic and ponderomotive effect on the self‐focusing of an intense right circularly polarized Gaussian laser pulse in magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al reported that the combined effect of a plasma density ramp and a magnetic field enhances the self‐focusing property of the laser beam. Theoretical investigations reveal that the presence of axial magnetic field not only decreases the laser spot size, but enhances the self‐focusing property of the circularly polarized and the linearly polarized laser beam . Sharma and Tripathi have investigated the relativistic and ponderomotive effect on the self‐focusing of an intense right circularly polarized Gaussian laser pulse in magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%